2005
DOI: 10.1103/physrevb.71.094515
|View full text |Cite
|
Sign up to set email alerts
|

Quantum point contact conductance in normal-metal/insulator/metal/superconductor junctions

Abstract: The effect of an insulating barrier located at a distance a from a NS quantum point contact is analyzed in this work. The Bogoliubov de Gennes equations are solved for NINS junctions (S: anysotropic superconductor, I: insulator and N: normal metal), where the NIN region is a quantum wire. For a = 0, bound states and resonances in the differential conductance are predicted. These resonances depend on the symmetry of the pair potential, the strength of the insulating barrier and a. Our results show that in a NIN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…On the other hand, the distance dependence for low energy and k F d >> 1 is in this case approximately 1/d 4 both for CAR and EC processes. In this orientation, the local Andreev reflection is zero because of diffraction of quasiparticles in the contact [35,36] and the CAR contribution to σ ba is not zero, but is always smaller than the EC one, leading to a negative non-local conductance as shown in Fig. 5.…”
Section: B Results For Dxy Symmetrymentioning
confidence: 93%
“…On the other hand, the distance dependence for low energy and k F d >> 1 is in this case approximately 1/d 4 both for CAR and EC processes. In this orientation, the local Andreev reflection is zero because of diffraction of quasiparticles in the contact [35,36] and the CAR contribution to σ ba is not zero, but is always smaller than the EC one, leading to a negative non-local conductance as shown in Fig. 5.…”
Section: B Results For Dxy Symmetrymentioning
confidence: 93%
“…Theoretically it has been shown that the effect of the magnetic field is to produce a shift of the ZES proportional to the applied magnetic field [11,12]. On the other hand studies of quantum point contacts in NIS junctions show that the ZBCP and ZES are removed by the quasiparticle diffractions at the point contact due to the vanishing of the Andreev reflection [13][14][15], an aspect that has been shown experimentally [6], where the width of the contact is reduced using a focused-ion beam technique. From the measurements it is concluded that, as the width is reduced, the relative ZBCP height decreases, indicating that Andreev reflections decrease.…”
Section: Introductionmentioning
confidence: 97%
“…When we consider a d xy symmetry the AR are suppressed by the diffraction in the interphase between the lead and superconductor [61]; thus, the processes that contribute to the shot noise are CAR, EC and Q. In NIS (N: normal-metal, I: Insulator, S: Superconductor) plane junctions, when the symmetry of the pair potential is d xy , a zero bias conductance peak (ZBCP) appears in the differential conductance due to the induction of states at the interface.…”
Section: D-wave Superconductorsmentioning
confidence: 99%
“…where f (k y ) is the weighting factor and is proportional to the perpendicular wave vector k xF [61], ξ is the superconductor coherence longitude defined as ξ(E, θ) = ξ 0 /Re[ 1 − E 2 /∆(θ)] and ξ 0 =hν F /(π∆ 0 ) the BCS coherence longitude. We write the retarded Green function of the uncoupled superconductorǧ r RR (E) aš g r S (E) = ĝ r S,aa (E)ĝ r S,ab (E) g r S,ba (E)ĝ r S,bb (E) ,…”
Section: Appendix a Modeling The Systemmentioning
confidence: 99%
See 1 more Smart Citation